Promusa: A global programme for Musa improvement: Proceedings of a meeting, 5-9 March 1997, Gosier, Guadalupa - Frison, Emile A.; Orjeda, G.; Sharrock, Suzanne L.; International Network for the Improvement of Banana and Plantain (1997)
The Guadeloupe meeting in march 1997 brought together some 70 of the most prominent researchers involved in Musa improvement world-wide. Discussions of the proposal global programme took place in both plenary and working group meetings and the programme strategy and the medium-termp plan have been defined. Five working groups were formed to address the major research areas: genetic improvement, Sigatoka disease, Fusarium wilt, nematology and virology. INIBAP / The World Bank